Proton beam therapy how protons are revolutionizing cancer treatment - Yajnik, Santosh. (Springer, 2013)
While radiation therapy is a mainstay of cancer treatment, traditional linear accelerators mainly use photons to irradiate cancerous tissue. Photons deposit much more energy in the surrounding normal tissue than protons. Proton beam therapy is a revolutionary alternative that deposits most of its cancer-killing energy within the area of the tumor, thereby potentially improving cure rates and reducing side effects in properly selected patients.  Proton Beam Therapy: How Protons Are Revolutionizing Cancer Treatment guides the reader through existing evidence supporting proton beam therapy for an increasing number of patients and conditions, including pediatric, prostate, and lung cancer, mediastinal tumors, skull base tumors, conditions of the eye, and sarcomas. An introduction to proton beam therapy -- Comparative treatment plans -- Proton beam therapy for pediatric conditions -- Proton beam therapy for prostate cancer -- Proton beam therapy for lung cancer -- Proton beam therapy for mediastinal tumors -- Proton beam therapy for the central nervous system -- Proton beam therapy for skull base tumors -- Proton beam therapy for conditions of the eye -- Proton beam therapy for sarcomas.